Brain connectome modularity in weight-restored anorexia nervosa and body dysmorphic disorder. Issue 13 (19th July 2016) - Zhang, A.; Leow, A.; Zhan, L.; GadElkarim, J.; Moody, T.; Khalsa, S.; Strober, M.; Feusner, J. D.
Abstract : Background: Anorexia nervosa (AN) and body dysmorphic disorder (BDD) frequently co-occur, and have several overlapping phenomenological features. Little is known about their shared neurobiology. The aim of the study was to compare modular organization of brain structural connectivity. Method: We acquired diffusion-weighted magnetic resonance imaging data on unmedicated individuals with BDD ( n = 29), weight-restored AN ( n = 24) and healthy controls (HC) ( n = 31). We constructed connectivity matrices using whole-brain white matter tractography, and compared modular structures across groups. Results: AN showed abnormal modularity involving frontal, basal ganglia and posterior cingulate nodes. There was a trend in BDD for similar abnormalities, but no significant differences compared with AN. In AN, poor insight correlated with longer path length in right caudal anterior cingulate and right posterior cingulate. Conclusions: Abnormal network organization patterns in AN, partially shared with BDD, may have implications for understanding integration between reward and habit/ritual formation, as well as conflict monitoring/error detection.